Cranioplasty Using a Novel Osteoconductive Scaffold and Platelet Gel. (March 2016) - Tseng, Ching-Li; Chang, Guang-Wei; OU, Kuang-Ling; Chou, Wei-Ting; Wu, Te-Hsing; Fang, Hsu-Wei; Tsai, Jui-Che; Chen, Tim-Mo
Abstract : Background: Commonly used materials for cranioplasty include autogenous bone grafts, methyl methacrylate, and titanium mesh. We evaluated a novel osteoconductive scaffold [ N -isopropylacrylamide cross-linked with acrylic acid using γ-rays (ANa powder)] mixed with platelet gel for cranioplasty. Methods: ANa powder mixed with platelet gel was implanted into a 15 × 15-mm, full-thickness calvarial bone defect in 5 New Zealand white rabbits. ANa powder mixed with phosphate-buffered saline was implanted in 5 rabbits. The calvarial bone defect was left unreconstructed in another 5 rabbits. Twelve weeks after surgery, computed tomography examination was used to evaluate the radiographic evidence of bone healing in vivo. Bone specimens were then retrieved for histologic study. Results: The ANa scaffold mixed with platelet gel is biocompatible, biodegradable, and both osteoconductive and osteoinductive, leading to progressive growth of new bone into the calvarial bone defect. Conclusion: The use of this novel osteoconductive scaffold combined with osteoinductive platelet gel offers a valuable alternative for the reconstruction of calvarial bone defects.